Helicobacter pylori Diversity and Gastric Cancer Risk - Timothy L. Cover (American Society for Microbiology, 2016)
ABSTRACT Gastric cancer is a leading cause of cancer-related death worldwide. Helicobacter pylori infection is the strongest known risk factor for this malignancy. An important goal is to identify H. pylori-infected persons at high risk for gastric cancer, so that these individuals can be targeted for therapeutic intervention. H. pylori exhibits a high level of intraspecies genetic diversity, and over the past two decades, many studies have endeavored to identify strain-specific features of H. pylori that are linked to development of gastric cancer. One of the most prominent differences among H. pylori strains is the presence or absence of a 40-kb chromosomal region known as the cag pathogenicity island (PAI). Current evidence suggests that the risk of gastric cancer is very low among persons harboring H. pylori strains that lack the cag PAI. Among persons harboring strains that contain the cag PAI, the risk of gastric cancer is shaped by a complex interplay among multiple strain-specific bacterial factors as well as host factors. This review discusses the strain-specific properties of H. pylori that correlate with increased gastric cancer risk, focusing in particular on secreted proteins and surface-exposed proteins, and describes evidence from cell culture and animal models linking these factors to gastric cancer pathogenesis. Strain-specific features of H. pylori that may account for geographic variation in gastric cancer incidence are also discussed.